Little robot - Hatke, Ben (First Second, 2015)
"When a little girl finds an adorable robot in the woods, she presses a button and accidentally activates him for the first time. Now, she finally has a friend. But the big, bad robots are coming to collect the little guy for nefarious purposes, and it's all up to a five-year-old armed only with a wrench and a fierce loyalty to her mechanical friend to save the day!" --